Pseudomonas 2008
DOI: 10.1002/9783527622009.ch13
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas–Plant Interactions

Abstract: Pseudomonas is a diverse genus containing a large number of species with a variety of catabolic and metabolic abilities. This diversity allows for the colonization of an array of environmental niches and interactions with a wide range of eukaryotic hosts as saprotrophs, endophytes, commensals, plant pathogens and opportunistic human pathogens [1][2][3][4][5]. Pseudomonas species are of great interest to researchers in the fields of plant, soil and human-associated microbiology, and as such the genomic sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 225 publications
(152 reference statements)
0
5
0
1
Order By: Relevance
“…The predominant phenazine produced in strain M18 is PCA, especially at 28°C, rather than PYO produced in other nosocomial originating P. aeruginosa strains [ 11 ]. Both PCA and Plt compounds produced by fluorescent Pseudomonas species are considered to play an important role in microbial competitiveness and combating plant pathogens [ 50 ]. To our knowledge, the strain M18 is the first strain that was reported to produce both PCA and Plt simultaneously, and the synergistic antibiotic effect of PCA and Plt can result in strong activity to protect plants from fungal phytopathogen infections.…”
Section: Resultsmentioning
confidence: 99%
“…The predominant phenazine produced in strain M18 is PCA, especially at 28°C, rather than PYO produced in other nosocomial originating P. aeruginosa strains [ 11 ]. Both PCA and Plt compounds produced by fluorescent Pseudomonas species are considered to play an important role in microbial competitiveness and combating plant pathogens [ 50 ]. To our knowledge, the strain M18 is the first strain that was reported to produce both PCA and Plt simultaneously, and the synergistic antibiotic effect of PCA and Plt can result in strong activity to protect plants from fungal phytopathogen infections.…”
Section: Resultsmentioning
confidence: 99%
“…Soil microorganisms are therefore considered an integral part of the soil phosphorus cycle. The use of bacterial inoculants as biofertilizers, which act to increase the levels of bioavailable phosphate in the rhizosphere, is seen as a potential component in modern environmentally friendly agricultural practices in terms of reducing the expense of phosphate fertilization (which is a finite resource), while maintaining suitable crop yields and reducing agricultural pollution (Morrissey et al., 2004; Vassilev et al., 2006; Miller et al., 2008). The ability to mineralize insoluble organic phosphates, such as phytates, phosphomono‐, di‐ and tri‐esters and organophosphonates via the actions of various phosphatase, phytase and phosphonatase enzymes, has been studied in several Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 99%
“…aureofaciens B-111 and B-306, since these fractions turned out to be toxic for indicator plants. At the same time, according to the literature [5,7], the protective effect of LPS is due to a part of the LPS molecule containing both lipid A and the associated OG-core.…”
Section: F I G 3 Electron Micrographs Of the Tmv And Lps Structural Components Interactionsmentioning
confidence: 98%
“…It`s known [5] that the antiviral effect of a number of natural substances of certain plant extracts does not exceed 40-50 %. Few reports indicate that some bacteria and yeasts [6,7] are capable of exhibiting antiviral activity. Thus, recently it has been shown that lipopolysaccharides (LPS) of some bacteria, in particular representatives of the genus Pseudomonas, play a significant role in the interaction of plants with pathogens [8].…”
mentioning
confidence: 99%